(untitled) (Altre Modernità, 2023)
This contribution carries out a spatial analysis of the short stories and poems collected in Giovanna Capone’s In My Neighborhood (2014), with a twofold aim: exploring the significance of physical and metaphorical liminalities in the development of Capone’s poetics and, on a more theoretical level, outlining an alternative paradigm, based on the concepts of liminality and communitas, to read Capone’s poetry, as well as other contemporary Italian-American literary texts. I identify four sites of liminality in Capone’s work and delve into their relationship with the narrative voice and the role they play in its evolution. This essay reflects on Giovanna Capone’s Bildung and her identity as a queer Italian-American author by re-reading the four spaces described in In My Neighborhood through the lens of Victor Turner’s theory of liminality and Roberto Esposito’s notion of communitas. Esposito’s development of the concept allows for an alternative interpretation of the community of Italian American queer subjectivities created by Capone in the Southwest. Finally, the connection of such community with Gloria Anzaldúa’s formulation of Borderland and ‘mestiza consciousness’ is highlighted as a theoretical counternarrative to the identification of the ethnic queer self as a member of a community defined by borders.